Improved simulation of thunderstorm characteristics and polarimetric signatures with LIMA two-moment microphysics in AROME - C. David; C. Augros; B. Vié; F. Bouttier; T. Le Bastard (Atmospheric Measurement Techniques)
Thunderstorm forecasting remains challenging despite advances in numerical weather prediction (NWP) systems. The microphysics scheme that represents clouds in the model partly contributes to the introduction of uncertainties in the simulations. To better understand the discrepancies, synthetic radar data simulated by a radar forward operator (applied to model outputs) are usually compared to dual-polarization radar observations, as they provide insight into the microphysical structure of clouds. However, the modeling of polarimetric values and radar signatures such as the ZDR column (ZDRC) remains a complex issue, despite the diversity of microphysics schemes and forward operators, especially above the freezing level where values that are too low are often found.